Factors Influencing E-Commerce Purchases of Halal Cosmetics: A UTAUT2 Approach - Fildza Shabrina Meta; Arif Imam Suroso; Asep Nurhalim (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The rapid growth of information technology has transformed business activities, particularly through e-commerce, which facilitates seamless transactions between producers and consumers. In Indonesia, internet penetration reached 78.19% in 2023, driving demand for halal cosmetics online and necessitating insights into consumer behavior to enhance market reach and trust.Purpose: This study identifies factors impacting consumer intentions in purchasing halal cosmetics online utilizing an extended UTAUT2 model with a Trust variable.Design/Methodology/Approach: This study utilizes a quantitative survey design to gather 260 responses from e-commerce users who purchase halal cosmetics. Structural Equation Modeling-Partial Least Squares (SEM-PLS) analyzed the relationship among variables.Findings: All performance expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, and trust are significant factors influencing the consumer intention and behavior. Among these, habits emerged as the most influential factor, indicating that habitual use is instrumental to the formation of purchasing behaviors.Conclusion: Based on these findings, it further suggests that the e-commerce platforms should put great effort into building consumer trust via robust security systems, thorough technical support, as well as personalized, fun shopping to ultimately help the halal cosmetics market to prosper.Originality/Value (State of the Art): This study incorporates Trust into the UTAUT2 model to improve understanding of strategies that will optimize halal e-commerce. Keywords: consumer behavior, e-commerce, halal cosmetics, trust, UTAUT2